The Features of bone destruction in rabbits with experimental metabolic syndrome - Mavlonov , Anvar; Saidov , Saidamir; Mirsultanov, Jakhongir; Boboeva , Rano (The Scientific Temper, 2024)
There is now evidence that abdominal obesity and metabolic syndrome in general are associated with a decrease in bone mineral density, which in turn leads to an increased risk of fractures. A high incidence of osteoporosis and vertebral fractures in patients with MS has been proven. Thus, MS can be considered a new risk factor for osteoporosis. We studied biochemical parameters in rabbits with experimental metabolic syndrome, accompanied by bone destruction, as well as in models of metabolic syndrome (MS) and osteoporosis. The level of glucose and c-peptide indicates the development of insulin resistance in animals with MS and MS, accompanied by bone destruction. It has been shown that with metabolic syndrome associated with bone destruction, rabbits exhibit more profound disorders of lipid metabolism than with MS, the level of which differs slightly from each other. The study of bone remodeling indicators in a model of MS accompanied by bone destruction showed individual and gender differences in the content of bone remodeling markers in blood serum. It has been shown that in most experimental animals there is a decrease in osteocalcin, which is a marker of osteosynthesis, and an increase in the level of type I collagen C-telopeptide, which indicates increased destruction of bone collagen. Moreover, the level of bone destruction was more pronounced in males than in females. A study of biomarkers of cartilage tissue degradation showed that the level of change in COMP and hyaluronic acid was higher in females than in males, and the deviation of aggrecan levels from the reference value was higher in males. From our results we can conclude that in male rabbits with MS, bone tissue damage predominated, while in females the degree of cartilage tissue damage was higher.